ADMINISTRASI WAKAF DI LOMBOK TIMUR (ANALISIS POTENSI SUMBER DAYA PENGEMBAGAN EKONOMI UMAT) - Zulkurnain Zulkurnain; Muslihun Muslihun; Muh. Salahudin (Nusantara Hasana Journal, 2021)
The general purpose of this research is to find out how waqf administration and its problems, to know the potential of economic development resources of the people in waqf administration in East Lombok Regency. The type of research in this research is field research using a qualitative approach. The process of collecting data in this study, researchers used the methods of observation, interviews, and documentation. The results of the study conclude that waqf administration in East Lombok is still relatively low because the number of waqf administration is still lacking, Nazhir as the manager does not have sufficient competence and knowledge, and the institutions authorized to waqf administration are still lacking in socializing The problems with waqf in East Lombok are: many people and religious leaders do not understand waqf regulations because they tend to view waqf as a charity, limited budget, and human resources so that the socialization carried out by the government is not evenly distributed to all nazhir, the small certification budget owned by the KUA and Ministry of Religion, so that part of the budget handed over to wakif or nazhir. The potential for the economic development of the people in the waqf administration in East Lombok shows large enough potential for utilization, seen from the total area of ​​waqf land, where the five waqfs observed, only the musholla in Masbagik District has limited waqf area. However, Nazhir as the waqf manager has not shown creativity or innovation to expand the utilization of this potential. However, Nazhir as the waqf manager has not shown creativity or innovation to expand the utilization of this potential.